"Baranda": structure and praxis of "Onibaranda" (micro-middlemen) in Yorubaland. Issue 3 (4th November 2020) - Oyekola, Isaac Akintoyese; Olajire, Oluyinka Olutola
Abstract : Purpose: This study aims to investigate the historical antecedent of baranda practice, marketing strategies of Onibaranda, as well as the benefits and challenges associated with baranda practice. Design/methodology/approach: Using exploratory research design, primary data were collected from 27 interviewees in two purposively selected markets in Ibadan. Responses were audio-taped, transcribed, proofread, categorized into themes and, finally, content analyzed to decrypt the underlying thought patterns and processes. Findings: The findings showed that the origin of the age-long practice of baranda was unknown. It was also discovered that Onibaranda used various, dynamic and situational marketing strategies to carve a niche for themselves, in response to the demand of the markets in which they operate. Lastly, the results showed that while some stakeholders see Onibaranda as useful and necessary marketing agents that uniquely connect sellers and buyers, others outline the ignoble role that Onibaranda play in their bid to create valuable exchanges between sellers and buyers. Practical implications: Knowledge of this study is germane to informal market stakeholders both in Yorubaland and across the globe. Social implications: Unless baranda practice is properly regulated, various ills associated with it might discredit the numerous benefits inherent in the practice. Concerted effort by all market stakeholders is, therefore, highly imperative so as to provide rules and regulations that will guide and check the excess practices of Onibaranda in the study locations, as this will enhance customer satisfaction, sellers' profits and smooth continued operation of Onibaranda. Originality/value: This empirical study represents the first attempt to examine the structure and praxis of Onibaranda in Ibadan.